Kajian keratan rentas mengenai pengetahuan, sikap dan amalan terhadap pencegahan demam denggi di Kampung Belawai, Sarikei dari 20 Jun hingga 5 Ogos 2000 - Ang Leng, Peow; Chew Kian, Peng; Lau Kiew, Siong; Nicholas Lim Lye, Tak; Ong May, Lea; Salawati, bt. Sanib; Stalia Wong Siew, Lee; Syarifah Hafizah, bt Wan Kasim; Wong Siong, Chuong (Universiti Malaysia Sarawak (UNIMAS), 2000)
A cross-sectional study was carried out in Kampung Belawai, Sarikei to assess the knowledge, attitude and practice of the villagers towards the prevention of Dengue Fever. The study was conducted from 20 July 2000 to 5 August 2000 by fourth year medical students from Faculty of Medicine and Health Sciences, Universiti Malaysia Sarawak (UNIMAS). A total of 232 respondents were selected based on systematic random sampling method and were interviewed by using a set of pre-tested questionnaire. A presumptive survey on Aedes larvae infestation rate was also carried out together with the interview. The majority of the respondents were female (61.3%). The results showed that the mean score for knowledge, attitude and practice of the general population was 53.5%, 69.7% and 45.7%, respectively. There was also significant association between knowledge, attitude and practice with sociodemographic factors such as age, education level and the household income. The Aedes larvae survey showed that the Breteau Index was 54.7, House Index was 33.6 and Container Index was found to be 14.4%. Pottery was the commonest container found to be infested with Aedes larvae. After the survey, an intervention program by the theme of `Hapuskan Denggi, Bekrwai Boleh! ' was carried out on 22nd and 23`d July 2000 at Kampung Belawai to raise the knowledge, attitude and practice of dengue prevention among the target population. The intervention program was also aimed to reduce the Aedes larvae infestation rate. It is recommended that continuous health education in small groups to be implemented among the target population to improve their knowledge, attitude and practice towards the prevention of Dengue Fever.